2021
DOI: 10.1186/s12916-021-02156-5
|View full text |Cite
|
Sign up to set email alerts
|

IRF7 and RNH1 are modifying factors of HIV-1 reservoirs: a genome-wide association analysis

Abstract: Background Combination antiretroviral treatment (cART) cannot eradicate HIV-1 from the body due to the establishment of persisting viral reservoirs which are not affected by therapy and reinitiate new rounds of HIV-1 replication after treatment interruption. These HIV-1 reservoirs mainly comprise long-lived resting memory CD4+ T cells and are established early after infection. There is a high variation in the size of these viral reservoirs among virally suppressed individuals. Identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 69 publications
0
10
4
Order By: Relevance
“…The second analysis demonstrated that there were no statistically significantly SNPs by "possible partial controller" status, in association with HIV reservoir size. Interestingly, several of the top (non-significant) SNPs identified from within the "possible partial controller" group were in or within 50 kb of immunologically relevant genes (Table S9), such as BRINP1, SNX29, IL1RAPL2, MX1, NFATC3, RIPK2, MASP2, TRIM6-TRIM34, HLA-A, and RNH1, the latter of which was reported as the top hit SNP from a recent genomewide association studiy of HIV reservoir size, as noted above (24). Finally, we only measured the peripheral CD4+ T cell reservoir, not the tissue reservoir, where the majority of HIV persists during treatment (107).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The second analysis demonstrated that there were no statistically significantly SNPs by "possible partial controller" status, in association with HIV reservoir size. Interestingly, several of the top (non-significant) SNPs identified from within the "possible partial controller" group were in or within 50 kb of immunologically relevant genes (Table S9), such as BRINP1, SNX29, IL1RAPL2, MX1, NFATC3, RIPK2, MASP2, TRIM6-TRIM34, HLA-A, and RNH1, the latter of which was reported as the top hit SNP from a recent genomewide association studiy of HIV reservoir size, as noted above (24). Finally, we only measured the peripheral CD4+ T cell reservoir, not the tissue reservoir, where the majority of HIV persists during treatment (107).…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, in order to identify host genetic variation associated with the HIV reservoir size, we performed custom whole exome sequencing and HLA typing among HIV noncontrollers, including a range of individuals treated during "early" (within 6 months) and "later" (after 6 months) of HIV infection from the University of California San Francisco SCOPE and Options cohorts. Our study adds to two recent host genetic studies of the HIV reservoir (23,24), one of which was published concurrently to ours (24). The first (23) evaluated 797 HIV-infected acute-and chronic-treated individuals from the Swiss Cohort Study, of which 194 had whole exome sequencing performed but observed no association between genetic variants (including HLA or CCR5∆32) and reservoir size.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Lymphocytes and monocytes were identified by granularity and size. Lymphocytes were further characterized using CD4, CD8, CD45RA and CCR7 to identify CD4+ cells and CD8+ naïve (CD45RA+CCR7+), central memory (CM, CD45RA-CCR7+), effector memory cells (EM, CD45RA-CCR7-), effector memory cells expressing CD45RA (TEMRA, CD45RA+CCR7-) and the total pool of effector memory cells (TEM, CD45RA-/+CCR7-) (41, 42). In addition, CD4+ naive regulatory (nTreg, CD45RA+CD25+) and CD4+ memory regulatory (mTreg, CD45RA-CD25++) cell subsets were identified.…”
Section: Methodsmentioning
confidence: 99%
“…For the PLHIV cohort, the genotyping, imputation, and quality control were described previously (41). In addition, for the healthy individuals, the genotyping, imputation, and quality control were performed as in the previous study (42).…”
Section: Genotypes Imputation and Quality Controlmentioning
confidence: 99%